2022
DOI: 10.1155/2022/8990629
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigation of the Immunoprotective Effect of Zinc on Ovalbumin Induced BALB/C Male Mice Based on NF‐KB Signaling Pathway

Abstract: Allergic rhinitis is one of the common chronic inflammatory diseases of the nasal mucosa. In order to investigate the effect of zinc on ovalbumin induced allergic rhinitis in BALB/C male mice based on NF-KB signaling pathway, thirty BALB/C male mice are randomly divided into three groups: control group, ovalbumin induced allergic rhinitis asthma group and zinc intervention group. The experimental results show that Zinc supplementation in allergic asthma mice with allergic rhinitis correct the immune response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%